ANALISIS PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENGATASI KESULITAN MEMBACA SISWA KELAS RENDAH DI SD MBS PRAMBANAN - Ridha Fadillah; Purwo Hari Handoko (Universitas Ahmad Dahlan, 2020)
The ability that must be possessed by the lower classes in Elementary School is the ability to read, but low grade students or novice readers usually have difficulty reading at low levels. To overcome this, it is necessary to have effective learning media in order to overcome reading difficulties in lower classes. This study aims to analyze the effectiveness of audio-visual learning media in overcoming the reading difficulties of low grade students at SD MBS Prambanan. The method used in this research is descriptive approach method, data obtained from research subjects are analyzed according to the statistical method used and interpreted by this type of qualitative research. Data collection was carried out by interviewing class II teachers at SD MBS Prambanan and distributing questionnaires to 15 low grade students. reading then analyzed using descriptive statistics with visual analysis techniques in the form of diagrams. The results showed that there was an increase in the level of reading difficulty after using audio visual learning media. This data can be strengthened by data from the results of the distribution of questionnaires that have been obtained. The data is in the form of a diagram which has a percentage of 90.9%, 100%, 90.9%, 100%, 100%, 81.8%, and 81.8% which, if averaged, is 92.2%. Based on this data, it can be concluded that the use of audio-visual learning media is quite effective in overcoming reading difficulties for low-grade students at SD MBS Prambanan.